2014
DOI: 10.1371/journal.pone.0110964
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Hepatic Iron and Fat by Dual-Source Dual-Energy Computed Tomography Based on Material Decomposition: An Animal Study

Abstract: ObjectiveTo explore the feasibility of dual-source dual-energy computed tomography (DSDECT) for hepatic iron and fat separation in vivo.Materials and MethodsAll of the procedures in this study were approved by the Research Animal Resource Center of Shanghai Ruijin Hospital. Sixty rats that underwent DECT scanning were divided into the normal group, fatty liver group, liver iron group, and coexisting liver iron and fat group, according to Prussian blue and HE staining. The data for each group were reconstructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 21 publications
0
27
0
4
Order By: Relevance
“…Thus, it would be difficult to differentially quantify these two metals because the attenuation of x-ray beams would be similar. Whereas some publications indicated that iron can be quantified from fat and iodinated contrast agents in phantoms or animal models (28)(29)(30), this work has not been extended to patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it would be difficult to differentially quantify these two metals because the attenuation of x-ray beams would be similar. Whereas some publications indicated that iron can be quantified from fat and iodinated contrast agents in phantoms or animal models (28)(29)(30), this work has not been extended to patients.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the increase in attenuation due to iron overload might mask or underestimate the HS because the coexistence of fatty infiltration and iron deposition may lead to almost normal attenuation of the liver. 44 To address this issue, both ex-vivo phantom study 45 and animal study 46 have shown promising accuracy of advanced dual energy CT techniques in quantifying liver fat even in the presence of iron and iodinated contrast media. However, results from patients are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…This scanner uses a three-material (soft tissue, fat, and contrast medium) decomposition algorithm. Ma et al previously demonstrated that the separation of hepatic iron from fat, using dual-source, DE-CT material decomposition with a threematerial algorithm, was feasible in vivo, even when iron and fat coexisted [25]. Currently, DE-CT applications in clinical settings are mainly used in chest, abdomen, and genitourinary diagnosis, and have been used since the DE-CT technique first became available on commercial CT machines [11].…”
Section: Discussionmentioning
confidence: 99%